STRATEGI PEMBELAJARAN PAKET C & B DENGAN MENGGUNAKAN MODEL PAKEM (PARISIPATIF, AKTIF, KREATIF DAN MENYENANGKAN) DALAM RANGKA MENINGKATKAN MUTU UNGGULAN PESERTA DIDIK (Studi Kasus UPT Pasar Sukatani Depok) - Enny Nurcahyawati; Hamidah Apriani (Media Nusantara, 2019)
National Education should ensure educational equity, improvement of quality,relevance and efficiency of education. According to the Law no. 20 in 2003,article 17 and 18 with regard to National Education System, it’s mentioned thatPaket A Program is equal to Primary Education (SD/MI), Paket B Programis equal to Lower Secondary Education (SMP/MTs) and Paket C is adequateto Upper Secondary Education (SMA/MA). Relating to that matter. Facingthe barriers and challenges of this millennium era, PAKEM Model LearningStrategy rooted from learning concept, should be based on student centred learningto create fun learning environments so that students are continually motivatedto learn which eventually lead the to become qualified and competent. as such current research objectives are to observe and analyse learning strategies of Paket B and C Program to gain the insight on the extent of academic result andskills of students participating in Paket B and C Program if associated with both current learning strategy and PAKEM Learning Model. Lastly, as for the design, this research customs qualitative method with Rolling Cloud Approaches